2018
DOI: 10.3390/polym10111187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Tapioca Starch on Mechanical, Thermal, and Morphological Properties of PBS Blends for Food Packaging

Abstract: In this study, polybutylene succinate (PBS) was blended with five types of modified tapioca starch to investigate the effect of modified tapioca starch in PBS blends for food packaging by identifying its properties. Tensile and flexural properties of blends found deteriorated for insertion of starch. This is due to poor interface, higher void contents and hydrolytic degradation of hydrophilic starch. FTIR results show all starch/PBS blends are found with footprints of starch except OH stretching vibration whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 46 publications
(51 reference statements)
4
52
0
1
Order By: Relevance
“…Presences of modified tapioca starch shows spherical shape embedded on the PBS surface. However, blending with tapioca starch show weak bonding as stated in previous work 40 . Figure 4c,d show starch particles and fibres are not well dispersed on the PBS matrix causing weak bonding, indicating fracture happens easily.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…Presences of modified tapioca starch shows spherical shape embedded on the PBS surface. However, blending with tapioca starch show weak bonding as stated in previous work 40 . Figure 4c,d show starch particles and fibres are not well dispersed on the PBS matrix causing weak bonding, indicating fracture happens easily.…”
Section: Methodssupporting
confidence: 60%
“…In this research, the author uses modified tapioca starch which has good processability compared with native starch. The used of modified tapioca starch also can reduce processing time for compound formation 16 . One study has investigated the processing properties and strength of composite from the blending of polyester with starch 17 .…”
mentioning
confidence: 99%
“…PBS is synthesized from succinic acid and 1,4-butanediol (BDO) via a polycondensation process, and exhibits balanced performance in thermal and mechanical properties as well as processability [ 5 ]. It is more thermally stable than PLA polymer [ 6 ]. PBS is able to undergo biodegradation and even disposal in compost, moist soil, fresh water (by activated sludge), or sea water.…”
Section: Introductionmentioning
confidence: 99%
“…Although these results were achieved for specific nanocomposites, they suggest that ternary PHA/PBSA/starch blends can show an affordable compatibility. On the other hand, some authors have shown that blends of PBS with starch showed a good adhesion at the interface [33], with an improved processability [34] that enabled these blends to be used in food packaging.…”
Section: Introductionmentioning
confidence: 99%